Marking DMEK Grafts Using Bandage Contact Lens Interface Technique: Doubling the Utilization During the Acute Shortage of Donor Corneas. Issue 4 (10th April 2022) - Basak, Samar K.; Basak, Soham
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to describe a novel bandage contact lens (BCL) interface technique for marking the Descemet membrane endothelial keratoplasty (DMEK) graft so that a single donor cornea can be used effectively for 2 recipients during acute shortage. Methods: This was a retrospective comparative case series. In group A, 37 eyes underwent DMEK using a graft marked by the ‟BCL interface technique" that was compared with 49 conventional DMEK grafts marked through the stromal window (group B). In group A, a resized BCL with a central 3-mm hole with the concavity up was placed between the stroma and peeled-off DM. This BCL with DM was flipped for S-stamping on the DM side. Final trephination was performed on a second Teflon block. The remaining anterior lamellar tissues of group A were used on the same day for other keratoplasty procedures. Endothelial cell density (ECD) and endothelial cell loss between the 2 groups were compared after 3 and 6 months. Results: The ECD at 3 months in group A (n = 35) versus group B (n = 45) was 2228 ± 270/mm 2 versus 2302 ± 254/mm 2 ( P = 0.48), and the ECD at 6 months (n = 23 and 22) was 2058 ± 324/mm 2 versus 2118 ± 260/mm 2 ( P = 0.72). The corresponding endothelial cell loss was 23.3% ± 6.8% versus 20.3% ± 6.1% ( P = 0.18) at 3 months and 29.1% ± 8.4% versus 26.7% ± 8.0% ( P = 0.34) at 6 months. Among anterior tissues of group A, 17 (45.9%) were used for deep anterior lamellar keratoplasty, 18 (48.6%) were used for larger therapeutic and tectonic grafts, and 2 were used as keratoprosthesis carriers. Donor detachment rate (8.6% vs. 8.9%) was similar in both groups without primary graft failures. Conclusions: The BCL interface technique is a simple and safe technique for stamping DMEK grafts. Anterior corneal tissues can be used for additional keratoplasties during donor shortage.